Prediksi Kecepatan Angin untuk Mengetahui Potensi Sumber Energi Alternatif menggunakan Model Regresi Lasso: Studi Kasus Kota Makassar pada Tahun 2024 - Siti Nurjanah; Yoan Purbolingga; Dila Marta Putri; Asde Rahmawati; Fahrizal Fahrizal; Bastul Wajhi Akramunnas (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
This research explores the potential of wind energy as an alternative energy source in Makassar City. The researcher used daily climate data from BMKG Martim Paotere Meteorological Station Makassar City for 2023 to January 2024. The research method uses the Lasso regression model to predict wind speed. The results of data processing, through tests with an MSE value of 0.334 and an R2 value of 0.97, show the high validity of the model. Wind speed predictions for 2024 were then generated and converted into estimates of the electrical power that could be generated. Based on this prediction, the maximum wind speed reached 10.76 m/s, with the maximum electrical power reaching 1597 Watts. The results of this study indicate that Makassar City has considerable potential to be developed as a Wind Power Plant location as an alternative source of electrical energy. This potential can contribute to reducing dependence on conventional energy in Makassar City.